PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE LEARNING TOGETHER (LT) DENGAN MEDIA AUDIO VISUAL PADA MATA PELAJARAN SEJARAH SEMESTER GENAP UNTUK MENINGKATKAN KESADARAN SEJARAH DAN HASIL BELAJAR SISWA KELAS XI IPS 1 SMA NEGERI GONDANGREJO TAHUN AJARAN 2015/2 - Mubarokah, Fitri; Djono, Djono; Yuniyanto, Tri (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
This research aims to determine how the teaching of history applying cooperative learning model using learning together (LT) type with audio visual media can increase the awareness of history and learning outcomes of the second grade students of Social 1 in Gondangrejo Senior High School. This research applies classroom action research which was held at Gondangrejo Senior High School even semester batch 2015/2016. The subject of the research is the students of Social 1 even semester of Gondangrejo Senior High School batch 2015/2016 with a total of 34 students. This research was conducted in two cycles with the stages of planning, acting, observing and reflecting. The data were analyzed using qualitative data analysis technique that consists of three main stages which are data collection, data reduction and conclusion. The result shown in the research can be concluded that application of cooperative learning model using learning together (LT) type with audio visual media can possibly increase the awareness of history and learning outcomes of the second grade students of Social 1 in Gondangrejo Senior High School. It can be seen from the percentage of awareness of history and the learning outcomes that achieve a specified target that is 80% for a minimum percentage of the classical sense of history and 75% for the percentage of classical completeness learning outcomes. After being given the action for two cycles, the results showed an increase in both the students? awareness of history and the student learning outcomes. The level of awareness of the history achieved by the students at the pre-cycle was 68%, it increased to 74% in the first cycle and 82% in the second cycle. Meanwhile, for the learning outcomes achieved by students in pre-cycle with an average of 65.53 in the first cycle increased to 72.41 and on the second cycle the percentage of classical completeness increased to 77,59 with 20.59% inthe pre-cycle in cycle, increased 44.11%in the first cycle and 76.47% in the second cycle.